Scaling Impact: Innovation for the Public Good - McLean, Robert; Gargani, John (Routledge, 2019)
Scaling Impact introduces a new and practical approach to scaling the positive impacts of research and innovation. Inspired by leading scien tific and entrepreneurial innovators from across Africa, Asia, the Car ibbean, Latin America, and the Middle East, this book presents a synth esis of unrivalled diversity and grounded ingenuity. The result is a d ifferent perspective on how to achieve impact that matters, and an imp ortant challenge to the predominant more-is-better paradigm of scaling . For organisations and individuals working to change the world for th e better, scaling impact is a common goal and a well-founded aim. The world is changing rapidly, and seemingly intractable problems like env ironmental degradation or accelerating inequality press us to do bette r for each other and our environment as a global community. Challenges like these appear to demand a significant scale of action, and here t he authors argue that a more creative and critical approach to scaling is both possible and essential. To encourage uptake and co-developmen t, the authors present actionable principles that can help organisatio ns and innovators design, manage, and evaluate scaling strategies. Sca ling Impact is essential reading for development and innovation practi tioners and professionals, but also for researchers, students, evaluat ors, and policymakers with a desire to spark meaningful change.
Keywords: Developing & Emerging Countries